Intergranular lattice misorientation mapping by synchrotron x-ray micro-beams: Laue vs energy-resolved Laue vs monochromatic reciprocal space analysis - Hofmann, F; Abbey, B; Song, X; Dolbnya, I; Korsunsky, A (World Scientific Publishing Company, 2010)
Laue diffraction, energy scanning and reciprocal space mapping are three micro-beam synchrotron X-ray diffraction techniques allowing the investigation of local misorientation induced by the dislocation substructure. In this paper a comparison between the three methods is presented, based on the mapping of a single 311 reflection from a grain within a Ni polycrystal specimen deformed to a tensile plastic strain of ~9%. Qualitatively it is observed that the maps obtained by different techniques all share the same features, although some deviations exist due to experimental limitations associated with each of the measurement techniques.